ULTRASONIC STUDIES OF POLYVINYLCHLORIDE IN CYCLOHEXANONE AND 1,4-DIOXANE - Thapa, B; Shrestha, P; Bhattarai, P (Scientific World, 2015)
Ultrasonic velocity and density were measured for the binary systems: polyvinylchloride—cyclohexanone and polyvinylchloride–1,4-dioxane. And hence, the acoustic impedance (Z) and reciprocal of adiabatic compressibility (?-1) were computed. The variations of ultrasonic velocity, density and acoustic impedance with concentration of polyvinylchloride were studied; confirming the absence of solute–solvent interaction. Scientific World, Vol. 12, No. 12, September 2014, page 62-64